Hacia la reorganización territorial de Asturias mediante las mancomunidades o uniones voluntarias de concejos - Fernández García, Aladino (Ería, 1989)
RESUMEN - RÉSUMÉ - ABSTRACT En Asturias, como en otras comunidades autónomas, se ha iniciado una reorganización administrativa y territorial sobre la base de las mancomunidades, que son agrupaciones voluntarias intermunicipales para la realización de obras y la prestación de servicios. Pero tales agrupaciones, para que acaben consolidándose y transformándose administrativamente en comarcas, necesitan de un mayor apoyo de la Comunidad Autónoma. * * * Vers une reorganisation territoriale d'Asturies moyennant des associations volontaires intermunicipales.- Une réorganisation administrative et territoriale a comencé à se produire en Asturies, aussi bien que dans d'autres communautés autonomes, appuyées sur les syndicats intermunicipaux, c'est à dire, des associations volontaires intermunicipales pour la réalisation de travaux publics et la prestation de services. Mais de telles associations ont besoin d'una plus grande aide afin de se consolider et de se transformer, d'un point de vue administratif, en contrées. * * * Towards a territorial reorganization of Asturias through voluntarily associations of municipalities.- In Asturias, like in other autonomic communities, an administrative and territorial reorganization has started on the basis of mancomunidades, i. e. groups of municipalities voluntarily associated in order to accomplish some proyects of civil engineering and give some services. But for such groups could consolidate and become administrative comarcas, a greater support from the Autonomic Community is needed. PALABRAS CLAVE: Concejo, mancomunidad, comarca, provincia, región, comunidad autónoma, reorganización territorial. MOTS CLÉS: Commune, syndicat intermunicipal, contrée, département, région, communauté autonome, réorganisation territorial. KEY WORDS: Municipality, mancomunidad, comarca, province, region, autonomic comunity, territorial reorganization.